2019
DOI: 10.1016/j.ceb.2019.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Switching states: dynamic remodelling of polarity complexes as a toolkit for cell polarization

Abstract: Polarity is defined by the segregation of cellular components along a defined axis. To polarize robustly, cells must be able to break symmetry and subsequently amplify these nascent asymmetries. Finally, asymmetric localization of signaling molecules must be translated into functional regulation of downstream effector pathways. Central to these behaviors are a diverse set of cell polarity networks. Within these networks, molecules exhibit varied behaviors, dynamically switching among different complexes and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 85 publications
(111 reference statements)
0
25
0
Order By: Relevance
“…The defining attribute of all epithelia is their apicobasally polarized morphology which is characterized by compartmentalized apical and basolateral domains comprising distinct repertoires of proteins and organelles. The apicobasally polarized state emerges as a consequence of the synchronized interplay between networks of polarity complexes which act to break symmetry and magnify asymmetry (reviewed in Peglion and Goehring, 2019). A major outcome of polarity network activity is the establishment of AJs which demarcate the border between the apical and lateral membranes.…”
Section: Interplay Between Ajs and Polarity Complexes Impose Rg Apicomentioning
confidence: 99%
See 1 more Smart Citation
“…The defining attribute of all epithelia is their apicobasally polarized morphology which is characterized by compartmentalized apical and basolateral domains comprising distinct repertoires of proteins and organelles. The apicobasally polarized state emerges as a consequence of the synchronized interplay between networks of polarity complexes which act to break symmetry and magnify asymmetry (reviewed in Peglion and Goehring, 2019). A major outcome of polarity network activity is the establishment of AJs which demarcate the border between the apical and lateral membranes.…”
Section: Interplay Between Ajs and Polarity Complexes Impose Rg Apicomentioning
confidence: 99%
“…Conversely, the Lgl/Dlg/Scribble complex maintains lateral identity by overriding Par complex activity (Yamanaka et al, 2003). Studies in invertebrates and in in vitro models (Peglion and Goehring, 2019) have shown that Par3 is localized to nascent sites of cell-cell adhesion and recruits Par6 and aPKC to the adjacent apical membrane. As the epithelial cell matures Par3 dissociates from Par6/aPCK in response to Cdc42-mediated aPKC phosphorylation and relocates to the cadherin adhesion complex, thereby stabilizing the apical domain and emerging AJs (Tanentzapf and Tepass, 2003;Yamanaka et al, 2003).…”
Section: Interplay Between Ajs and Polarity Complexes Impose Rg Apicomentioning
confidence: 99%
“…How intracellular protein gradients, such as the CES-1 Snail gradient described here, are established is not fully understood. Studies in the one-cell C. elegans embryo suggest that diffusion-state switching and long-range cortical flows can generate stable protein gradients (Cheeks et al, 2004;Folkmann and Seydoux, 2018;Goehring et al, 2011;Munro et al, 2004;Peglion and Goehring, 2019;Wu et al, 2018). Furthermore, asymmetric cortical contractility and local cortical extension have been shown to contribute to the partitioning of proteins during the asymmetric divisions of D. melanogaster neuroblasts (Chugh and Paluch, 2018;Loyer and Januschke, 2020;Tsankova et al, 2017).…”
Section: Roles For Actomyosin Network In Nsm Neuroblast Divisionmentioning
confidence: 99%
“…Intrinsically motile cells can spontaneously switch to a migratory polarized phenotype [47]. Understanding complex molecular circuits employed by a cell to establish polarization has been studied both theoretically [2,19,31,32,36,42] and experimentally [6,45,49,70].Polarity establishment arises primarily through the localization of particular proteins and lipids in the cell to specific regions of the plasma membrane, and often precedes motility. Experiments have identified a few conserved sets of proteins involved in polarization including the PAR system [37, 44], the Wnt system [28], the Scribble complex [3,58], and the Rho system [6,55].…”
mentioning
confidence: 99%
“…Intrinsically motile cells can spontaneously switch to a migratory polarized phenotype [47]. Understanding complex molecular circuits employed by a cell to establish polarization has been studied both theoretically [2,19,31,32,36,42] and experimentally [6,45,49,70].…”
mentioning
confidence: 99%